The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1039/c9cc08749d
|View full text |Cite
|
Sign up to set email alerts
|

1,3-Carboboration of iodonium ylides

Abstract: Herein, we disclose the utilisation of iodonium ylides to access a range of boron dienolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…A limitation of this reaction was that cyclic iodonium ylides (e. g., 1 c , 1 d ) failed to produce any of the desired O−H insertion products in all attempts. This result is consistent with such ylides being inherently more stable than their acyclic counterparts, [42] possibly due to better anionic stabilization by the planar β‐dicarbonyl motif, or due to secondary bonding between this motif and iodine [43] …”
Section: Resultssupporting
confidence: 81%
“…A limitation of this reaction was that cyclic iodonium ylides (e. g., 1 c , 1 d ) failed to produce any of the desired O−H insertion products in all attempts. This result is consistent with such ylides being inherently more stable than their acyclic counterparts, [42] possibly due to better anionic stabilization by the planar β‐dicarbonyl motif, or due to secondary bonding between this motif and iodine [43] …”
Section: Resultssupporting
confidence: 81%
“…First, the reaction begins with the formation of phenyl‐Rh species through initial transmetallation of [Cp*RhCl 2 ] 2 and organoboron reagent [34] . Both H 2 O and CIY have the potential to facilitate this process, probably due to their abilities to form boron‐′ate′ species with organoboron compounds [35,13f] . Next, the coordination of iodonium ylide ( 10 ) to the metal center of the Ph−Rh species gives intermediate B , which further generates the Rh‐carbene intermediate C by loss of iodobenzene (carbenation process).…”
Section: Resultsmentioning
confidence: 99%
“…In 2020, Melen et al described an original access to dienolate-coordinated borinic acids by carboboration of iodonium ylides ( Scheme 58 ) [ 179 ]. They showed that mixing triarylboranes 171 with an equimolar amount of acyclic symmetrical or unsymmetrical iodonium ylides in toluene afforded compounds 173a–d in good yields.…”
Section: Cleavage Of One C-b Bondmentioning
confidence: 99%